Registration of Clearfield 'CLL15' southern long‐grain rice. Issue 2 (14th April 2021) - Esguerra, Manuel Q.; Sha, Xueyan; Hardke, Jarrod T.; Scott, Robert C.; Wamishe, Yeshi; Counce, Paul A.; Bateman, Nick; Beaty, Bryan A.; Bulloch, Jill M.
Abstract: 'CLL15' (Reg. no. CV‐154, PI 692952) is a high‐yielding, very early maturing, short‐stature Clearfield (BASF) long‐grain rice ( Oryza sativa L.) cultivar with improved disease package developed by the University of Arkansas Rice Research and Extension Center in Stuttgart, AR, and approved for release by the Arkansas Agricultural Experiment Station, University of Arkansas System Division of Agriculture in January 2019. It was selected from the cross of RU1302048/RU1302045 made in summer 2013. CLL15 was initiated as a F4 bulk of a single progeny row in the winter nursery near Lajas, Puerto Rico, in spring 2015. From 2016 to 2019, CLL15 was evaluated in 47 multilocation trials. Clearfield cultivars 'CL151', 'CL153', and 'CL172' served as checks. Grain yield of CLL15 was 9.33 t ha −1 across all trials compared with 9.50 t ha −1 for 'CL151', 8.74 t ha −1 for CL153, and 8.74 t ha −1 for CL172. However, in the multilocation trials in Arkansas—Arkansas Rice Performance Trial and Producer Rice Evaluation Program—CLL15 consistently produced the highest grain yield, ranging from 8.80 to 10.31 t ha −1 . Plant height of CLL15 was 97 cm, which is 2 cm taller than CL172, but shorter than 101 cm for CL151 and 99 cm for CL153. CLL15 reached 50% heading in 83 d, which was similar to CL151 and 2 d earlier than both CL153 and CL172. CLL15 is moderately resistant to blast and susceptible to sheath blight, bacterial panicle blight, kernel smut, and false smut. Core Ideas: Clearfield long‐grain cultivar CLL15 was developed by University of Arkansas. CLL15 is high yielding, very early maturing, and short stature. CLL15 is adapted to rice growing conditions throughout Arkansas and the U.S. mid‐South.